Alternative Mechanisms of Service Delivery : Legal and Regulatory Review, Volume 1. Main Text - World Bank (Washington, DC, 2013)
This report reviews the Indonesian legal and regulatory framework that might support or obstruct the promotion of alternative mechanisms of service delivery (AMSD). AMSD, as it has been translated in Indonesian, is a term used especially in Canada to describe an array of strategies and tools that government can use to deliver services in "not the normal way'. 'Alternative' is used in the sense of 'alternative lifestyle" or 'not traditional'. The objectives of the project in relation to promoting AMSD within regional governments are: i) assistance to government in the rationalization of different institutional arrangements for the delivery of sub-national public services; and ii) aid in the development and implementation of new (contracting) methods for service delivery. The report aims to describe the current proximate legal and regulatory framework within which the eight strategies work. The report provides the basis for understanding where the strategies already have 'support' and where the framework needs improving or additions.